Potensi Tumbuhan Berkhasiat Obat di Hutan Penam Ketungau Kabupaten Sintang - Fathul Yusro; Gusti Hardiansyah; Erianto Erianto; Yeni Mariani; Denni Nurdwiansyah; Hendarto Hendarto; Aripin Aripin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Forests are a source of plant biodiversity whose existence and benefits are very large for humans, one of which is medicinal plants. The purpose of this study was to identify the types and analyze the potential of medicinal plants found in the Penam Ketungau Forest, Empaka Kabiau Raya Village, and Karya Bakti Village, Sintang Regency. This study uses a survey method with a sampling design in the form of systematic sampling with random start. A cluster is made in the form of a square and at each corner and in the middle a plot is made (5 plots) with the shape of a circle (radius 17.8 m). Each plot contained 5 circular subplots in the form of a seedling subplot with a radius of 1 m, 2 m stake, 5 m pole, and 17.8 m tree. The plant species obtained were identified and potential data (density and relative density) at each growth stage were analyzed. The results obtained 45 species of medicinal plants, and the species with the greatest potential were at the seedling level (6000 individuals/Ha (29.27%)) and saplings (2375 individuals/Ha (37.25%)) namely Hopea mengerawan Miq, Dryobalanops Dyer oblongifolia at the pole level (40 individuals/Ha (25%)) and Hopea borneensis at the tree level (43.21 individuals/Ha (13.46%)). The still good condition of the forest, the large potential, and the variety of medicinal plant species identified in the Penam Ketungau Forest indicate the success of the efforts made by the community around the forest and the Sintang District Government in maintaining and protecting the Penam Ketungau Forest, so that in the future it is necessary to improve the status of the Penam Ketungau Forest. become a High Conservation Value (HCV) forest.